Influence of wattle on udder measurements and milk yield of Red Sokoto (Maradi) does raised semi-intensively in Minna, Niger state, Nigeria. - Kolo, P.S.; Alemede, I.C.; Egena, S.S.A.; Adama, J.Y.; Banjo, A.A.; Otu, B.O.; Abubakar, M.B.; Agboba, K.; Maidariya, H.A.; Omolade, C.; Okike, C.; Idajili, G.; et al. (Nigerian Journal of Animal Science, 2023)
A study on the Influence of wattle in Red Sokoto (Maradi) goats on udder measurements, colostrum/milk quantity and quality was carried out at the Teaching and Research Farm of the Department of Animal Production, Federal University of Technology, Minna. Thirty-six (36) Red Sokoto goats comprising of thirty-two (32) does and four (4) bucks, managed semi-intensively, were used for the study. Parameters observed included udder circumference, distance between teats, change in udder circumference, change in distance between teats, teat length after milking, milk quantity and quality analysis. After the experiment, it was observed that crosses between the wattle and the non[1]wattled had the highest (p <0.05) udder circumference before and after milking, quantity of milk and average daily milking. Wattled does crossed with non-wattled bucks in T3 and Wattled does crossed with wattled bucks in T4) produced the highest (p><0.05) peak yield. Wattled does mated with wattled bucks (T4) had the highest (p><0.05) total milk yield. Wattled does mated with wattled bucks (T4) had the (p><0.05) highest moisture content in colostrum sample which reduced the availability of other minerals. Non-wattled does mated with non-wattled bucks (T1) and wattled does mated with wattled bucks (T4) had the highest (p><0.05) moisture content in the milk sample which reduced the availability of most minerals in the milk. In conclusion, attention should be focused on the crosses between the wattled and the non-wattled Red Sokoto as it gave best result in most parameters examined. Deliberate effort must be made to preserve the wattle gene to prevent the goats carrying the gene from going into extinction.>